Socio-environmental conflict, citizen participation and territorial dispute: Contributions from Community Environmental Psychology - René Squella Soto; Pontificia Universidad Católica de Valparaíso (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2021)
The planet is suffering a phenomenon of global warming and climate change in which the neoliberal capitalist development model has great responsibility as the main actor of the socio-environmental problems that are leading us to a new era of extinction. In Chile, under the current model, the conflicts in which the territory is disputed as well as the valuations that are made of it and the common goods existing there are multiplying. The present research, with the perspective of the Community Environmental Psychology, and the collective mapping as a methodological tool, together with the Socio Environmental Movement "No to Thermoelectric Plant of Quebradilla", La Ligua (Valparaíso Region, Chile), describes and analyses the socio environmental conflicts that occur in the Province of Petorca, together with the practices of citizen participation that the communities carry out defending their territory. Within the results, out of the conflict an organized collective action emerges from the community, stimulating the sustainable construction of the territory that the inhabitants have generated for decades, and challenging authorities and institutions by stopping a project classified as harmful to the ecosystem and local productive initiatives.